Psicodin??mica do trabalho com servidores em est??gio probat??rio - Camargo, Davi Fernando de (2017)
This thesis aims at analyzing the psychodynamics of work related to public employees on probationary period from a Public Foundation using as methodology the psychodynamic of work. The probationary period is considered a sensitive, determinant and decisive stage in the professional life of the public employee, with individual, institutional and social repercussions. The theoretical framework used is the psychodynamics of work, advocated by Dejours (1992; 2004), having as its practical-methodological development the psychodynamic work clinic. The clinic represents the opportunity of an accessible and safe space for the expression and resignification of the working life of the subject. The study conducted eight clinic sessions with the participation of eleven public employees and five clinicians, with each session enduring for about sixty minutes. All the meetings were recorded and transcribed in full. The content analysis technique was used in order to organize the results and discussions in the following categories: a) work organization, b) meaning of work, c) subjective mobilization and pleasure at work, d) suffering, and e) Defensive strategies. It has been noted that the work organization is rigid, computerized and allows for rare opportunities for participation and discussion; however, on the other hand, it offers substantial institutional benefits such as remuneration, stability and the status of being a public employee. It has been found that it is the employee himself, in most cases, who gives meaning to his work, mobilizes himself, feels pleasure, suffers and defends himself, basing himself mainly on the choices available or on the mere glimpse of another work possibility or even another reality. The suffering appears in the relations with the leadership, in the discredit attributed to the evaluation of performance, as well as in the meeting between the prescribed and the real, considering that what is prescribed in the selection process is different from the activity performed, mostly characterized by monotony and repetition, with little room for modifications and contributions, and thus not sufficient for proper upward mobilization. There is cooperation, but one that is only related to technical aspects connected to work demands. It is noticed the absence of collective coping strategies to what bothers the employees. It was identified that they do not have the sense of belonging to the Foundation, understanding the probationary period as a passing professional stage. Finally, the study shows the development of the psychodynamic of work, within a specific envirment, to make visible the suffering at work and the subjective mobilization. Nevertheless, in the group studied, there was a limitation of the clinic regarding the possibility of producing greater interference and involvement of the workers in the context in which they work: there is a general perception, among the majority of the participants, that the current position is provisional and the change of public office something certain. This limited the number of sessions held, as well as demonstrated the non-engagement of workers in the quest towards changing the organization in which they work, since there is an individual quest to change jobs.